THE INFLUENCE OF NETWORK BUILDING ON THE INNOVATIVE WORK BEHAVIOUR OF SELF-MONITORING INDIVIDUALS: INTEGRATING PERSONALITY AND SOCIAL CAPITAL PERSPECTIVES - NASAJ, MOHAMED (2020)
Network building ability is an important skill that has positive implications for individuals’ innovative work behaviour. Although high self-monitors are capable of building strategic relationships, little is known about how this capability helps these individuals innovate in service organisations, particularly generating, promoting and realising innovative ideas. We proposed that network building ability may act as an important mediator through which self-monitoring links to innovative work behaviour. Using structural equation modelling to analyse 417 completed questionnaires from employees in the United Arab Emirates service sector, we found that high self-monitors were more likely to have high network building abilities, which in turn help support their innovative work behaviour. The evidence suggests that network building ability fully mediates the relationship between self-monitoring and idea generation and idea promotion, while partially mediating the relationship between self-monitoring and idea realisation. We discuss the theoretical contributions and managerial implications of the study.